Lymphomatoid granulomatosis. Case Presentation - Marisela García de la Torre; Yanelka Bouza Jiménez; Stephany Milagros Acosta País; Maribel Misa Menéndez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
The case of a 21-year-old male patient is presented, who on December 30, 2017 began with increased volume, flushing and heat in the right lateral region of the neck, after the presence of a boil in the occipital region of the scalp. Treatment with antibiotic was started, but erythe-matopapular lesions appeared on the trunk and extremities that were interpreted as a medication adverse reaction. He started with a maintained fever of 38 0C, malaise, weight loss, hepatomegaly and small non-painful adenopathies in the inguinal and axillary regions, so he was admitted on January 14, 2018 at the Gustavo Aldereguía Lima Hospital in Cienfuegos and was treated with antibiotic before a hematological profile which indicated associated sepsis. A fine-needle aspiration was performed, which was negative and arrangement for biopsy was made. On January 15, the clinical condition of the patient worsened with high fever, disorientation, marked excitement, awareness and respiratory insufficiency, and he died on the 16th. Autopsy revealed lymphomatoid granulomatosis as the main cause of death.